Fundamental biomaterials : polymers - Thomas, Sabu; Balakrishnan, Preetha; Sreekala, Meyyarappallil Sadasivan (Woodhead Publishing, 2018)
Fundamental Biomaterials: Polymers provides current information on findings and developments of biopolymers and their conversion from base materials to medical devices. Chapters analyze the types of polymers and discuss a range of biomedical applications. It is the first title in a three volume set, with each reviewing the most important and commonly used classes of biomaterials and providing comprehensive information on classification, materials properties, behavior, biocompatibility and applications. The book concludes with essential information on wear, lifetime prediction and cytotoxicity of biomaterials. This title will be of use to researchers and professionals in development stages, but will also help medical researchers understand and effectively communicate the requirements of a biomaterial for a specific application. Further, with the recent introduction of a number of interdisciplinary bio-related undergraduate and graduate programs, this book will be an appropriate reference volume for large number of students at undergraduate and post graduate levels.- Resumé vydavatel
Keywords: biologické materiály; biopolymery; biotechnologie; biomedicína; biological materials; biopolymers; biotechnology; biomedicine; učebnice vysokých škol; kolektivní monografie; elektronické knihy; textbooks (higher); collective monographs; electronic books